Policy interactions in large‐scale marine protected areas. Issue 1 (22nd August 2020) - Gruby, Rebecca L.; Gray, Noella J.; Fairbanks, Luke; Havice, Elizabeth; Campbell, Lisa M.; Friedlander, Alan; Oleson, Kirsten L.L.; Sam, King; Mitchell, Lillian; Hanich, Quentin
Abstract: Large‐scale marine protected areas (LSMPAs) have proliferated in recent years, now accounting for most of the world's MPA coverage. However, little is known about LSMPA outcomes and the factors that affect them. Here we argue that policy interactions—the cumulative effect of co‐existing policies for an issue and/or geographical area—can play a critical, but under‐recognized, role in influencing LSMPA design and outcomes. We analyze interactions between national LSMPAs within Palau and Kiribati, and regional fisheries management established by the Nauru Agreement to show how policy actors can account for policy interactions in LSMPA design, and to demonstrate the profound influence that policy interactions can have on the economic and conservation outcomes of LSMPAS. We draw on our analysis to distill lessons for our case studies and LSMPAs globally. We emphasize that policy interactions are dynamic and malleable: they should be proactively managed to stimulate synergy and address conflict. Understanding and managing policy interactions is complex and context‐specific, requiring dedicated resources, cross‐sectoral coordination, and sophisticated scientific and practical policy expertise. To avoid undesirable consequences and capitalize on opportunities to secure multiple benefits, we recommend that policy actors systematically evaluate, monitor, and adapt to policy interactions throughout LSMPA design and implementation.